Characterizing primate home-ranges in Amazonia: Using ferns and lycophytes as indicators of site quality - Cárdenas Ramírez Glenda Gabriela; Jones Mirkka M; Heymann Eckhard W; Tuomisto Hanna (WILEY, 2022)
The habitats present in research sites across Amazonia have usually been characterized only very broadly, for example, as inundated or non-inundated (terra firma) forests. However, within each of these categories there is considerable variation in soil properties and floristic composition. This variation is likely to determine habitat quality for animal populations through its effects on primary productivity and food availability, thereby affecting carrying capacity. Therefore, comparison of edaphic properties across sites could provide new insight into which factors affect animal foraging patterns, population densities, and home-range sizes. We provide an example from Estacion Biologica Quebrada Blanco in Peruvian Amazonia, where behavioral studies on primates (especially tamarins) have been conducted for more than three decades but little is known about the edaphic or floristic characteristics of the forest they occupy. We used indicator plant species to estimate and map soil base cation concentration and its variability at Estacion Biologica Quebrada Blanco. We found that soils in the study area are relatively cation-poor in a western Amazonian context, which probably translates into low primary productivity. Some differences in soils among the home-ranges of three tamarin groups were also observed, illustrating the usefulness of the method for detailed habitat mapping.in Spanish is available with online material.